2019
DOI: 10.29332/ijhs.v3n1.244
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between social skills and alcohol consumption

Abstract: It was considered necessary to conduct a literature review with the following objective: Determine the relationship between social skills and alcohol consumption. As a result of the theoretical review carried out, it was possible to identify that numerous authors emphasize that social skills are important protective factors against alcohol consumption. On the other hand, the deficit in social skills is associated with the appearance of substance use. In addition, there are studies that point to the social inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Findings on association between third year of study and drug use are comparable to an eight year longitudinal analysis in Mid-Atlantic that reported highest annual peak of marijuana use in year three of study (8). This could be attributed to factors like academic-related stress (24), poor social skills thus increased vulnerability to peer pressure to use drugs (25), limited physical activities (26) and poor quality dating relationships (27). All the aforementioned factors combined increased vulnerability to stress and depression which in turn heightens drug use as a form of self medication.…”
Section: Discussionsupporting
confidence: 58%
“…Findings on association between third year of study and drug use are comparable to an eight year longitudinal analysis in Mid-Atlantic that reported highest annual peak of marijuana use in year three of study (8). This could be attributed to factors like academic-related stress (24), poor social skills thus increased vulnerability to peer pressure to use drugs (25), limited physical activities (26) and poor quality dating relationships (27). All the aforementioned factors combined increased vulnerability to stress and depression which in turn heightens drug use as a form of self medication.…”
Section: Discussionsupporting
confidence: 58%
“…This could be attributed to factors like academic-related stress [ 63 ], poor social skills, thus increased vulnerability to peer pressure to use drugs [ 64 ], limited physical activities [ 65 ], and poor quality dating relationships [ 66 ]. All the aforementioned factors combined increase vulnerability to stress and depression which in turn heighten drug use as a form of self-medication.…”
Section: Discussionmentioning
confidence: 99%
“…There are several impacts of alcohol use among young adults, particularly those who are attending university or college, such as reduced learning capability [ 28 ], deprived coping skills [ 29 ], and condensed social skills [ 30 ]. Several studies [ 15 , 21 , 24 ] have reported that different characteristics such as sex, age, living away from home, parental education, household income, and tobacco use, contribute to the prevalence of alcohol use.…”
Section: Introductionmentioning
confidence: 99%